Optical response of fiber bragg grating to the strain - Norzaimah Asyikim Mohd. Zaidi, 1990-; Bashir Tahir, supervisor; Fakulti Sains (2011)
Project Paper (Sarjana Muda Sains (Fizik Industri)) - Universiti Teknologi Malaysia, 2011